Drosophila Sister-of-Sex-lethal reinforces a male-specific gene expression pattern by controlling Sex-lethal alternative splicing. Issue 5 (27th December 2018) - Moschall, Rebecca; Rass, Mathias; Rossbach, Oliver; Lehmann, Gerhard; Kullmann, Lars; Eichner, Norbert; Strauss, Daniela; Meister, Gunter; Schneuwly, Stephan; Krahn, Michael P; Medenbach, Jan
Abstract: In Drosophila, female development is governed by a single RNA-binding protein, Sex-lethal (Sxl), that controls the expression of key factors involved in dosage compensation, germline homeostasis and the establishment of female morphology and behaviour. Sxl expression in female flies is maintained by an auto-regulatory, positive feedback loop with Sxl controlling splicing of its own mRNA. Until now, it remained unclear how males prevent accidental triggering of the Sxl expression cascade and protect themselves against runaway protein production. Here, we identify the protein Sister-of-Sex-lethal (Ssx) as an inhibitor of Sxl auto-regulatory splicing. Sxl and Ssx have a comparable RNA-binding specificity and compete for binding to RNA regulatory elements present in the Sxl transcript. In cultured Drosophila cells, Sxl-induced changes to alternative splicing can be reverted by the expression of Ssx. Moreover, in adult male flies ablation of the ssx gene results in a low level of productive Sxl mRNA splicing and Sxl protein production in isolated, clonal cell populations. In sum, this demonstrates that Ssx safeguards male animals against Sxl protein production to reinforce a stable, male-specific gene expression pattern.